Acute kidney injury to chronic kidney disease transition: insufficient cellular stress response. Issue 4 (July 2018) - Strausser, Sarah A.; Nakano, Daisuke; Souma, Tomokazu
Abstract : Purpose of review: Recent epidemiological and preclinical mechanistic studies provide strong evidence that acute kidney injury (AKI) and chronic kidney disease (CKD) form an interconnected syndrome. Injured kidneys undergo a coordinated reparative process with an engagement of multiple cell types after injury; however, maladaptation to the injury subjects kidneys to a vicious cycle of fibrogenesis and nephron loss. In this review, we will outline and discuss the pathogenesis of AKI-to-CKD transition with an emphasis on dysregulated 'cellular stress adaptation' as a potential therapeutic target. Recent findings: Recent studies identify the crucial role of injured tubular epithelial cells in the transition from AKI to CKD. Damaged tubular cells undergo reactivation of developmental and epithelial–mesenchymal transition signaling, metabolic alteration, and cell-cycle arrest, thereby driving inflammation and fibrogenesis. Recent work highlights that cellular stress-adaptive pathways against hypoxic and oxidative stress provide insufficient protection after severe AKI episode. Summary: Insufficient cellular stress adaptation may underpin the persistent activation of inflammatory and fibrogenic signaling in damaged kidneys. We propose that harnessing cellular stress-adaptive responses will be a promising therapeutic strategy to halt or even reverse the deleterious process of AKI-to-CKD transition.